The impact of personality trait on the relationship of emotional intelligence and self-esteem - Johar, Siti Sarawati; Ani, Fauziah; Zainol, Nur Zainatul Nadra; Saparudin, Intan Farhana; Panatik, Siti Aisyah (Institut of Research and Jurnal, 2017)
Fundamental science of psychology often rooted in diversity theory that touching reality of human and humanity. Theoretical solution alone may not be able to unlock the psychological issues because it is closely related to affective, cognitive and human behaviour in the workplace. In this study, the issues in the workplace are referring to personality, emotional intelligence and self-esteem of employees. The specific purpose of this study was to test the effect of extraversion personality as a moderator towards the relationship of emotional intelligence and self-esteem of employees. A total of 196 civil servants in the Local Authority (LA) have been selected as respondents. Measurement tools that used is Eysenck Personality Questionnaire-Revised Short Form (EPQR-S), Emotional Intelligence Self-Description Inventory (EISDI), and Rosenberg Self-Esteem Scale (RSES). The data was analysed by using the hierarchical regression analysis. The finding shows that the two hypotheses are accepted. From this analysis as well, there was a moderating effect of extraversion personality on the relationship between emotional intelligence (perception and appraisal of emotion, and understanding emotions) with self-esteem of employees. The most important finding shows that extraversion personality serves as moderator when the relationship between emotional intelligence and self-esteem are enhanced if extraversion were on a high level. This is compared with the low levels of extraversion personality that causing on relationship of emotional intelligence with self-esteem more weaker.